Mapping the environmental pressure due to economic factors. The case of Italian coastal municipalities - Modica, Marco; Zoboli, Roberto; Pagliarino, Elena (Argomenti, 2017)
In this paper we quantitatively characterize the main characteristics of the coastal municipalities from the point of view of sector specialization that may impact the environment of the Italian coastal municipalities. More in details, we first quantified settlement pressure on the Italian coasts, then we provide a detailed analysis of economic specializations by sectors of coastal municipalities. Finally, we develop a more specific analysis on the specialization and dependence of coastal municipalities. Focusing on two specific groups of economic sectors: i) those that depend on the sea as the primary source input (tangible and intangible) and ii) those that do not depend on the sea but that have high environmental pressures. We provide evidence of the relationship between sectors depending from the sea, i.e. ‘marine’ sectors and sectors that have a high pressure on the environment, i.e. ‘high pressure’ sectors in coastal municipalities. The analysis is based on municipal data of the Census of Industry and Services of 2011 provided by ISTAT on seven selected Italian regions: Campania, Emilia Romagna, Friuli-Venezia Giulia, Liguria, Apulia, Sardinia and Veneto.